Sodium Propionate Alleviates Atopic Dermatitis by Inhibiting Ferroptosis via Activation of LTBP2/FABP4 Signaling Pathway - Xie A; Li W; Ye D; Yin Y; Wang R; Wang M; Yu R (Journal of Inflammation Research)
Anni Xie,1,* Weijia Li,2,* Danni Ye,1 Yue Yin,3 Ran Wang,1 Min Wang,1 Renqiang Yu1 1Department of Neonatology, Affiliated Women’s Hospital of Jiangnan University, Wuxi Maternity and Child Health Care Hospital, Wuxi, 214002, People’s Republic of China; 2Department of Biochemistry and Molecular Biology, Franklin & Marshall College, Lancaster, PA, 17603, USA; 3Suzhou Medical College, Soochow University, Suzhou, 215123, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Wang; Renqiang Yu, Department of Neonatology, Affiliated Women’s Hospital of Jiangnan University, Wuxi Maternity and Child Health Care Hospital, Wuxi, 214002, People’s Republic of China, Tel +86 510 82725161, Fax +86 510 82725094, Email wangmin2072@163.com; yurenqiang@jiangnan.edu.cnBackground: Atopic dermatitis (AD) is a common pediatric skin disease, with recent studies suggesting a role for ferroptosis in its pathogenesis. Sodium propionate (SP) has shown therapeutic potential in AD, yet its mechanism, particularly regarding ferroptosis modulation, remains unclear. This study aims to explore whether SP alleviates AD by modulating ferroptosis-related pathways through bioinformatic and in vitro analyses.Methods: We analyzed the GEO AD cohort (GSE107361). Ferroptosis-related genes was compiled from the GeneCards Database and SP-associated therapeutic target genes were obtained from Swiss Target Prediction. To explore potential biological mechanisms, we employed Gene Set Variation Analysis (GSVA), Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Weighted Gene Co-expression Network Analysis (WGCNA) and differential expression analysis identified key gene modules. We also established TNF-α/IFN-γ induced AD cell models using HaCat cells and collected cell samples for further experiments.Results: The GSVA analysis demonstrated that ferroptosis-related genes could differentiate between healthy children and those with AD. The identified module includes genes with correlated expression patterns specifically linked to AD. Analysis using three algorithms identified potential therapeutic targets of SP. We screened 51 key genes related to AD and ferroptosis, selecting cyclin-dependent kinase 1 (CDK1) and latent transforming growth factor beta binding protein 2 (LTBP2) as co-expressed genes. Machine learning identified fatty acid binding protein 4 (FABP4) as a significant gene intersection of the 51 key genes. The bioinformatics analysis results were validated through cell experiments, showing that SP treatment increased the expression of the damaged skin genes loricrin (LOR) and filaggrin (FLG).Conclusion: Our study indicates that SP may alleviate AD symptoms by modulating ferroptosis through the LTBP2/FABP4 pathway.Keywords: atopic dermatitis, ferroptosis, bioinformatics, propionate